2019
DOI: 10.1007/s11069-019-03756-4
|View full text |Cite
|
Sign up to set email alerts
|

Inter-comparison of model, satellite and in situ tropical cyclone heat potential in the North Indian Ocean

Abstract: The North Indian Ocean (NIO) experiences frequent tropical cyclones (TCs). TC heat potential (TCHP) is a major ocean parameter responsible for TC genesis and intensification changes. In this study, Indian National Centre for Ocean Information Services-Global Ocean Data Assimilation System (INCOIS-GODAS) model and satellite-derived TCHP data from National Remote Sensing Centre (NRSC) and National Oceanic and Atmospheric Administration (NOAA) are validated against TCHP from in situ profiles in the NIO during the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 43 publications
(46 reference statements)
0
3
0
Order By: Relevance
“…The build-up of TCHP since March 2020 can be seen for both boxes and this increased TCHP (also considered as ocean heat content) acts as preconditioning to sustain the MHW and tropical cyclone. Previous studies showed that subsurface ocean warming can play a key role in the generation of MHWs (Elzahaby and Schaeffer, 2019;Scannell et al, 2020) as well as tropical cyclones (Jangir et al, 2020(Jangir et al, , 2021.…”
Section: Role Of Subsurface Warmingmentioning
confidence: 99%
See 1 more Smart Citation
“…The build-up of TCHP since March 2020 can be seen for both boxes and this increased TCHP (also considered as ocean heat content) acts as preconditioning to sustain the MHW and tropical cyclone. Previous studies showed that subsurface ocean warming can play a key role in the generation of MHWs (Elzahaby and Schaeffer, 2019;Scannell et al, 2020) as well as tropical cyclones (Jangir et al, 2020(Jangir et al, , 2021.…”
Section: Role Of Subsurface Warmingmentioning
confidence: 99%
“…This study focuses on the Bay of Bengal (BoB; Figure 1) whose dynamics are very complex due to the strong stratification from freshwater input, high SST values, and its vulnerability toward tropical cyclones that form during the pre-monsoon (March-May) and post-monsoon (October-November) seasons. The North Indian Ocean accounts for the highest number of fatalities globally from tropical cyclones (Mohanty et al, 2015), and the BoB experiences ∼5 to 7% of the total number of tropical cyclones that occur globally each year (Neetu et al, 2012;Jangir et al, 2020Jangir et al, , 2021. Out of 23 recorded deadly storms with fatalities > 10,000 in the last 300 years, 20 tropical cyclones formed over the BoB (Mohanty et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…TC landfalls are known to be dangerous and devastating natural disasters with huge effects on life, property and ecosystem throughout the world and thus are multi-hazard weather phenomena (Anthes 2016;Jangir et al 2020). A TC is a large atmospheric system comprising a rapid inward circulation of air masses with a low-pressure centre and accompanied by stormy destructive weather.…”
Section: Tropical Cyclonesmentioning
confidence: 99%